2019
DOI: 10.1002/ncp.10326
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in Cardiac Surgery

Abstract: Selenium (Se) is an essential trace element that plays a pivotal role in many of the body's regulatory and metabolic functions, especially during times of stress. After uptake, Se is incorporated into several Se-dependent proteins, which have potent antiinflammatory and antioxidant capacities. Several observational clinical studies have demonstrated that Se deficiency can cause chronic cardiovascular diseases and aggravate organ dysfunction after cardiac surgery and that low levels of Se may be independently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 90 publications
(118 reference statements)
0
4
1
Order By: Relevance
“…In 2019, anesthesiologists in Germany published a review study discussing the effects of low levels of preoperative Se level on patient's outcomes following the surgery. Unlike the result of the present study, they revealed that low levels of Se may cause chronic cardiovascular disease and also lead to organ dysfunction, such as kidney dysfunction in patients following the cardiac surgery (24).…”
Section: Discussioncontrasting
confidence: 99%
“…In 2019, anesthesiologists in Germany published a review study discussing the effects of low levels of preoperative Se level on patient's outcomes following the surgery. Unlike the result of the present study, they revealed that low levels of Se may cause chronic cardiovascular disease and also lead to organ dysfunction, such as kidney dysfunction in patients following the cardiac surgery (24).…”
Section: Discussioncontrasting
confidence: 99%
“…A recent report identified the protein in urine as a novel and early biomarker of acute kidney injury [29] and we described increased SELENBP1 concentrations in patients with acute coronary syndrome at high risk of major cardiac events [30]. Cardiac surgery negatively affects Se status and Se deficiency increases the risk of ischaemic heart disease [31] and promotes organ dysfunction after cardiac surgery [32]. To better characterize circulating SELENBP1 as a biomarker of myocardial stress, we monitored its concentration in patients undergoing surgery with cardioplegia-induced myocardial arrest and the use of a cardio-pulmonary bypass (CPB) and evaluated its potential diagnostic value with respect to convalescence and survival.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that selenium, a component of several antioxidant enzymes, is essential during oxidative stress due to its antioxidant and anti-inflammatory properties [ 14 ]. Diminished selenium levels have been independently associated with the development and aggravation of organ dysfunction, systemic inflammatory response, ischemic reperfusion injury, and higher mortality after cardiac surgery [ 15 , 16 ]. Studies have shown that selenium is not only protective against perioperative oxidative tissue damage but can also suppress IRI-induced leukocytosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%